KEPEMIMPINAN PENDIDIKAN PERSPEKTIF MANAJEMEN PENDIDIKAN - M. Sahabuddin; Syahrani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Trust is very important in a management. Good management is supported by good leadership. Leadership is founded on trust. When self-confidence is fragile, the leader will soon collapse. Similar to leadership standing in education on the basis of trust. Therefore, the most basic and important thing when being a leader is to instill trust in the members or subordinates because of the way that a leader will be respected and respected in an organization. Instilling trust in the leadership of subordinates is influenced by the type of person and the type of leadership style depends on the person.